Assessment of Fallopian Tube Epithelium Features Derived from Induced Pluripotent Stem Cells of Both Fallopian Tube and Skin Origins - Yu-Hsun Chang; Kun-Chi Wu; Kai-Hung Wang; Dah-Ching Ding (Cells, 2023)
Fallopian tube epithelial cells (FTECs) play a significant role in the development of high-grade serous ovarian cancer (HGSOC), but their utilization in in vitro experiments presents challenges. To address these limitations, induced pluripotent stem cells (iPSCs) have been employed as a potential solution, driven by the hypothesis that orthologous iPSCs may offer superior differentiation capabilities compared with their non-orthologous counterparts. Our objective was to generate iPSCs from FTECs, referred to as FTEC-iPSCs, and compare their differentiation potential with iPSCs derived from skin keratinocytes (NHEK). By introducing a four-factor Sendai virus transduction system, we successfully derived iPSCs from FTECs. To assess the differentiation capacity of iPSCs, we utilized embryoid body formation, revealing positive immunohistochemical staining for markers representing the three germ layers. In vivo tumorigenesis evaluation further validated the pluripotency of iPSCs, as evidenced by the formation of tumors in immunodeficient mice, with histological analysis confirming the presence of tissues from all three germ layers. Quantitative polymerase chain reaction (qPCR) analysis illuminated a sequential shift in gene expression, encompassing pluripotent, mesodermal, and intermediate mesoderm-related genes, during the iPSC differentiation process into FTECs. Notably, the introduction of WNT3A following intermediate mesoderm differentiation steered the cells toward a FTEC phenotype, supported by the expression of FTEC-related markers and the formation of tubule-like structures. In specific culture conditions, the expression of FTEC-related genes was comparable in FTECs derived from FTEC-iPSCs compared with those derived from NHEK-iPSCs. To conclude, our study successfully generated iPSCs from FTECs, demonstrating their capacity for FTEC differentiation. Furthermore, iPSCs originating from orthologous cell sources exhibited comparable differentiation capabilities. These findings hold promise for using iPSCs in modeling and investigating diseases associated with these specific cell types.